Kecerdasan Emosional, Dukungan Sosial dan Kecenderungan Burnout - Robiatul Adawiyah, Raden Adjeng (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. This research aimed to find the relationships of emotional intelligence, social support and teachersâ€™ tendency to burnout. Subjects of the study were teachers of SMAN 3 Bangkalan. Data were collected by scales of emotional intelligence, social support and tendency to burnout, and then analyzed by statistical regression and partial correlation. ResultsÂ  showed relationships significantly between emotional intelligence, social support and tendency to burnout. There was a negative correlation between emotional intelligence and tendency to burnout. There was a negative correlation between social support and tendency to burnout.Keywords: emotional intelligence, social support, burnoutÂ